Increasing of SIgA serum levels may reflect subclinical intestinal involvement in non-radiographic axial and peripheral spondyloarthritis (2020)
Objective The evidence shows that previous infection with enteric pathogens is a requirement to develop pSpA. Based on our previous results, variances on regulation of SIgA might influence SpA activity; thus, the aim of this study was to correlate the levels of SIgA, IgA against some enteric bacteria, and IL-17, IL-21, and IL-6 with clinical features in a group of SpA patients. Methods Twenty-six pSpA, 20 nr-axSpA, 60 healthy volunteers (HV), and 34 patients with inflammatory bowel diseases (IBD) were included. All subjects were assessed to measure SIgA, total and specific IgA for enteric bacteria, and IL-17, IL-21, and IL-6 levels and clinical variables. For SpA patients, the diagnosis was verified 5 years after first evaluation to assess the risk of developing r-axSpA. Results SIgA levels were significantly higher in SpA patients than in HV and IBD (p < 0.0001 and p = 0.047, respectively). However, no differences for SIgA neither total IgA were found among the SpA subtypes (p = 0.624). Only IL-6 was higher in SpA than HV (p = 0.013). An inverse correlation was demonstrated for SIgA and BASFI (r: − 0.45; p = 0.003), BASDAI (r: − 0.39; p = 0.0123), ASDAS-CRP (r: − 0.37; p = 0.014), and ASDAS-ESR (r: − 0.45; p = 0.0021). There was no evidence of risk of developing r-axSpA in patients who previously showed high levels of serum antibodies. Conclusion The results show that pSpA as well as nr-axSpA share a similar SIgA-intestinal involvement independently of a previous infection. This suggests that serum SIgA increases are evidence of subclinical intestinal compromise which could have influence on disease activity but not in this progression.